Macromolecular Crowding as a Tool to Screen Anti-fibrotic Drugs: The Scar-in-a-Jar System Revisited - Puerta Cavanzo, Nataly; Bigaeva, Emilia; Boersema, Miriam; Olinga, Peter; Bank, Ruud A. (Frontiers in Medicine, 2021)
An unsolved therapeutic problem in fibrosis is the overproduction of collagen. In order to screen the effect of anti-fibrotic drugs on collagen deposition, the Scar-in-a-Jar approach has been introduced about a decade ago. With macromolecular crowding a rapid deposition of collagen is seen, resulting in a substantial decrease in culture time, but the system has never been tested in an adequate way. We have compared six different macromolecular crowders (Ficoll PM 70 (Fc70), Ficoll PM 400 (Fc400), a mixture of Ficoll 70 and 400 (Fc70/400), polyvinylpyrrolidone 40 (PVP40), polyvinylpyrrolidone 360 (PVP360), neutral dextran 670 (ND670), dextran sulfate 500 (DxS500), and carrageenan) under profibrotic conditions (addition of TGFβ1) with primary human adult dermal fibroblasts in the presence of 0.5 and 10% FBS. We found that (1) collagen deposition and myofibroblast formation was superior with 0.5% FBS, (2) DxS500 and carrageenan results in an aberrant collagen deposition pattern, (3) ND670 does not increase collagen deposition, and (4) carrageenan, DxS500 and Fc40/700 affected important phenotypical properties of the cells when cultured under pro-fibrotic conditions, whereas PVP40 and PVP360 did less or not. Because of viscosity problems with PVP360, we conclude that PVP40 is the most optimal crowder for the screening of anti-fibrotic drugs. Finally, the effect of various concentrations of Imatinib, Galunisertib, Omipalisib or Nintedanib on collagen deposition and myofibroblast formation was tested with PVP40 as the crowder.